2019
DOI: 10.1158/1535-7163.mct-18-0341
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effector Functions of Human IgG2 Antibodies against EGFR

Abstract: Three FDA-approved epidermal growth factor receptor (EGFR) antibodies (cetuximab, panitumumab, necitumumab) are clinically available to treat patients with different types of cancers. Interestingly, panitumumab is of human IgG2 isotype, which is often considered to have limited immune effector functions. Unexpectedly, our studies unraveled that human IgG2 antibodies against EGFR mediated effective CDC when combined with another noncrossblocking EGFR antibody. This second antibody could be of human IgG1 or IgG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 68 publications
2
23
0
1
Order By: Relevance
“…Unlike IgG2 type antibodies, the specific response functions of IgG1 mainly include ADCC and CDC ( 41 ). Panitumumab is a human IgG2 isotype, which is often considered to have limited immune effector functions ( 42 ). Most of these antibodies are humanized or chimeric antibodies with reduced immunogenicity and antigen affinity.…”
Section: Anti-tumor Mechanisms and Effects Of Egfr Mabsmentioning
confidence: 99%
“…Unlike IgG2 type antibodies, the specific response functions of IgG1 mainly include ADCC and CDC ( 41 ). Panitumumab is a human IgG2 isotype, which is often considered to have limited immune effector functions ( 42 ). Most of these antibodies are humanized or chimeric antibodies with reduced immunogenicity and antigen affinity.…”
Section: Anti-tumor Mechanisms and Effects Of Egfr Mabsmentioning
confidence: 99%
“…54 Recently, it has been demonstrated that EGFR-specific IgG2 can induce CDC and ADCC. 55 This underlines the necessity of using Fc mutations to reduce FcγR interaction also for this supposedly less Fccompetent IgG subclass. In this study, IgG2 displayed a clearly inferior cellular clustering capacity, which is likely caused by reduced flexibility.…”
Section: Discussionmentioning
confidence: 97%
“…M1 macrophages can inhibit tumor development by releasing tumor-suppressing molecules, including TNF-a (45). M1 macrophages also induce tumor cell apoptosis through phagocytosis (46), ADCC (47), and release of TNF and nitric oxide (NO) (48). Studies have shown that M1-type macrophages can promote tumor immunity by recruiting cytotoxic T cells (49).…”
Section: Antitumor Effects Of Macrophagesmentioning
confidence: 99%